Parasite infection in Serranus cabrilla (Perciformes, Serranidae): histopathological aspects and new host record for nematode genus Philometra from Aegean Sea, Turkey - INNAL, D.; STAVRESCU-BEDIVAN, M.M.; OZMEN, O. (Journal of the Hellenic Veterinary Medical Society, 2020)
This study was conducted to determine infection with nematode parasite Philometra sp. in gonads of Serranus cabrilla recorded in Izmir Gulf between October 2016 and July 2017. The overall prevalence was 14.46% and the mean intensity of infection 1.2 parasites per fish. The occurrence of philometrid infection on comber hosts was assessed according to several risk factors (fish length class, sex and season). Our findings suggest that the highest rates of parasite infection occur in larger sized fish, hermaphrodite individuals and during April month. The present report also revealed that marked hyperemia was the major findings of infected gonads of S. cabrilla, where parasitic nematodes caused a marked inflammatory reaction at the histopathological examination. As far as we know, this paper represents the first mention of genus Philometra in S. cabrilla from Turkey and the first presence of philometrid parasites in Aegean coast of Turkey. Furthermore, the present work is the first record of the effects of Philometra sp. parasitism on a serranid species in Izmir Gulf.